Blade (New Line platinum, ,, 1998)
Wesley Snipes, Stephen Dorff and Kris Kristofferson star in this blood-chilling thriller about an action hero who uses his awesome powers and razor-sharp weaponry to hunt down the most ruthless killers the world has ever known.

Dark city (New Line platinum, ,, 1998)
When John Murdoch awakens in a strange hotel room, he finds that he is wanted for a series of brutal murders. The problem is he can't remember a thing. Pursued by the police and haunted by the Strangers, mysterious beings who possess the ability to stop time and alter reality, he seeks to unravel the twisted riddle of his identity. But in a city where reality is the ultimate illusion, discovering the truth could be fatal.

The lord of the rings: The two towers (New Line platinum, ,, 2009)
While Frodo Baggins and his friend Samwise continue on to Mordor to destroy the one ring, their allies launch assaults on Isengard, Helm's Deep, and the corrupt wizard Saruman.
Disc 1, Side A. Theatrical version, pt. 1; Extended version, pt. 1 , disc 1, side B. Theatrical version, pt. 2; Extended version, pt. 2 , disc 2. Special features.

Lord of the rings: the return of the king (New Line platinum, 0.00,, 2006)
Frodo Baggins and the Fellowship continue their quest to destroy the One Ring and stand against the evil of the dark lord Sauron. The Fellowship has divided and now find themselves taking different paths to defeating Sauron and his allies. Their destinies now lie at two towers - Orthanc Tower in Isengard, where the corrupted wizard Saruman waits and Sauron's fortress at Baraddur, deep within the dark lands of Mordor. DVD features the theatrical and extended versions of the film and a new documentary.
Disc 1, Side A. Theatrical version, pt. 1; Extended version, pt. 1 , disc 1, side B. Theatrical version, pt. 2; Extended version, pt. 2 , disc 2. Special features.

Secondhand lions (New Line platinum, ,, 2009)
This comedic and touching family film follows the adventures of a shy young boy who is sent to spend the summer with his eccentric uncles. At first shocked by his uncles' unconventional behavior that includes ordering African lions through the mail, the boy soon becomes enthralled with unraveling the mystery that has followed the uncles for years. Hearing tales of their exotic adventures involving kidnapped princesses, Arabian sheiks and lost treasure, not only brings him closer to his uncles but also teaches him what it means to believe in something -- whether it's true or not.
Disc 1 , Disc 2.

The notebook (New Line platinum, ,, 2005)
Behind every great love is a great story. Based on the best selling book from Nicholas Sparks, two teenagers from opposite sides of the tracks fall in love during one summer together, but are tragically forced apart. When they reunite seven years later, their passionate romance is rekindled, forcing one of them to choose between true love and class order.
Special features: Deleted/alternate scenes ; Optional feature commentary with director Nick Cassavetes ; Optional feature commentary with novelist Nicholas Sparks ; All in the family: Nick Cassavetes ; Nicholas Sparks: a simple story, well told ; Southern exposure: locating The notebook ; casting ; theatrical trailer ; DVD-ROM features including weblinks, script to screen, and more.